Improvement of the mechanism for recovering alimony for the maintenance of a minor child under the legislation of the Republic of Kazakhstan - Shadanova, L.Zh. (Bulletin of the Karaganda University “Law Series”, 2022)
The article analyzes the problems of protecting the right of a child to receive maintenance from his parents and other family members, which are guaranteed by the Constitution and family legislation of the Republic of Kazakhstan. The purpose of the study is to analyze the norms of the legislation that regulate the procedure for collecting alimony for the maintenance of minor children, as well as to consider and propose effective mech-anisms for solving the problems of non-execution of judicial acts on the recovery of alimony in the cases where a parent evades the obligation to support a child. Comparative-legal, dialectical, formal-legal methods were used. As a result, the authors of the study provided theoretical conclusions and proposals for improving family legislation and law enforcement practice in ensuring the right of the child to receive maintenance from his parents and other family members. The article concludes that the recovery of alimony should not act as a measure of property liability of the other parent. It is necessary to improve the mechanism for collecting ali-mony and to create a system that will stimulate the debtor’s responsibility to fulfill his obligations. One of the ways to pay off debts on alimony in case of default by parents on alimony obligations is the payment of bene-fits to a minor child from state funds for the material support of children from single-parent families.